2021
DOI: 10.1186/s13018-021-02211-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tirobot-assisted vertebroplasty in treating thoracolumbar osteoporotic compression fracture

Abstract: Background Percutaneous kyphoplasty is the main method in the treatment of thoracolumbar osteoporotic compression fractures. However, much radiation exposure during the operation harms the health of surgeons and patients. In addition, the accuracy of this surgery still needs to be improved. This study aimed to assess the radiation exposure and clinical efficacy of Tirobot-assisted vertebroplasty in treating thoracolumbar osteoporotic compression fracture. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…Various robot-assisted orthopedic surgery (RAOS) is currently available on the market, each addressing specific surgeries and characterized by a series of special features that may involve different requirements or modus operandi. RAOS has been utilized in a variety of orthopedic operations, including fracture fixation for traumatic surgery, total hip and total knee arthroplasty [ 18 , 19 ], spine surgery [ 20 , 21 ], bone tumor surgery [ 22 ], arthroscopy [ 23 ], and fracture fixation for traumatic surgery [ 24 ]. However, robotic in fracture reduction remains at an infant stage.…”
Section: Discussionmentioning
confidence: 99%
“…Various robot-assisted orthopedic surgery (RAOS) is currently available on the market, each addressing specific surgeries and characterized by a series of special features that may involve different requirements or modus operandi. RAOS has been utilized in a variety of orthopedic operations, including fracture fixation for traumatic surgery, total hip and total knee arthroplasty [ 18 , 19 ], spine surgery [ 20 , 21 ], bone tumor surgery [ 22 ], arthroscopy [ 23 ], and fracture fixation for traumatic surgery [ 24 ]. However, robotic in fracture reduction remains at an infant stage.…”
Section: Discussionmentioning
confidence: 99%
“…Xu HT et al proposed a navigation system that supported correct puncturing in PVP working with the C-arm tracker, patient tracker, and puncture needle tracker adjusting the spinal image information [ 28 ]. Wang B et al proposed a method for guiding punctures in Balloon kyphoplasty (BKP) using a system consisting of a reference tracker, a robotic arm, and a monitor [ 29 ]. As a unique attempt, the 3D-printer was used to create a puncture guide adapter for PVP, which had two sockets for inserting needles [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robot group: TiRobot system (Tinavi Medical Technologies Co., China) was used as previously detailed [ 16 ] . First, the tracer was fixed to the spinous process of the injured vertebrae in the caudal 2–3 segments with an original device and reinforced with a sterile film.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the Tirobot robot has been used in PKP for OVCF in spinal surgery. Preliminary clinical results have shown that robotic assistance can reduce surgical trauma, fluoroscopic exposure, and cement leakage [ 16 – 18 ] . However, the efficacy of robot-assisted PKP for multi-segmental OVCF remains unclear.…”
Section: Introductionmentioning
confidence: 99%